Effects of Different Human Milk Oligosaccharides on Growth of Bifidobacteria in Monoculture and Co-culture With Faecalibacterium prausnitzii - Cheng, Lianghui; Kiewiet, Mensiena B. G.; Logtenberg, Madelon J.; Groeneveld, Andre; Nauta, Arjen; Schols, Henk A.; Walvoort, Marthe T. C.; Harmsen, Hermie J. M.; de Vos, Paul (Frontiers in Microbiology, 2020)
Human milk oligosaccharides (hMOs) are important bioactive components in mother milk contributing to infant health by supporting colonization and growth of gut microbes. Especially Bifidobacterium genus are considered to be supported by hMOs. Approximately 200 different hMOs have been discovered and characterized, but only a few abundant hMO can be produced in sufficient amounts to be applied in infant formula. These hMOs are usually supplied in infant formula as single molecule and it is unknown which and how individual hMOs support growth of individual gut bacteria. To investigate how individual hMOs influence growth of several relevant intestinal bacteria species, we studied the effects of three hMOs (2’-fucosyllactose, 3-fucosyllactose, 6’-sialyllactose) and an hMO acid hydrolysate (lacto-N-triose) on three Bifidobacteria and one Faecalibacterium, and introduced a co-culture system of two bacterial strains to study possible cross-feeding in presence and absence of hMOs. We observed that in monoculture, B. longum subsp. infantis could grow well on all hMOs but in a structure-dependent way. F. prausnitzii reached a lower cell density on the hMOs in stationary phase compared to glucose, while B. longum subsp. longum and B. adolescentis were not able to grow on the tested hMOs. In a co-culture of B. longum subsp. infantis with F. prausnitzii, different effects were observed with the different hMOs, 6’-sialyllactose, rather than 2’-fucosyllactose, 3-fucosyllactose, and lacto-N-triose, was able to promote the growth of B. longum subsp. infantis. Our observations demonstrate that effects of hMOs on infant gut microbiota is hMO specific and provides new effective ways of supporting growth of specific beneficial microorganisms in the intestine.